Effects of cinnamon extract on blood sugar levels of type 2 diabetes mellitus patients: Randomized Controlled Trial (RCT) - Dilma'aarij Agustia; Sutan Sahala Muda Marpaung; Dita Anggriani Lubis (AcTion: Aceh Nutrition Journal, 2025)
Cinnamon is an herbal remedy proven to lower blood sugar levels in patients with type 2 diabetes mellitus (DM). Cinnamon contains coumarin, which reduces the blood sugar levels. This study aimed to determine whether administration of a higher dose of cinnamon could lower blood sugar levels in individuals with type 2 diabetes mellitus. Methods: This study employed a randomized controlled trial (RCT) design and was conducted at the Medan Denai Health Center from November to December 2023. Participants were randomly selected and divided into two groups: the intervention group, which received cinnamon extract (n= 15), and the control group (n= 15), which did not receive any treatment. The dose was 10 mg/day. Blood sugar levels were measured using a standardized instrument and data were analyzed using the Kruskal–Wallis test. Results, before receiving cinnamon extract, the average blood sugar level was 238,80 mg/dL in the intervention group and 225,33 mg/dL in the control group. After cinnamon extract administration, the intervention group showed a significant reduction of 127,73 mg/dL, whereas that of the control group remained at 222,20 mg/dL. Statistical analysis revealed a significant difference in the blood sugar levels following cinnamon extract administration (p< 0,001). In conclusion, cinnamon extract supplementation can help lower blood sugar levels in patients with type 2 diabetes mellitus.